F. S. DICKINSON, JR. Biohazard Science Training Program. (American Journal of Public Health)
The article reports on the graduate training program sponsored by Mr. and Mrs. F. S. Dickinson Jr. The biohazard science graduate training option was offered at the Department of Parasitology and Laboratory Practice School of Public Health of the University of North Carolina, Chapel Hill campus. The training program includes laboratory courses, lectures, seminars and field trips while topics covered in the program includes laboratory and institutional infections, review of chemical, radiological and biological safety, safety management and other biohazards.